Prevalence and factors associated with depression among the elderly in rural areas of Kannur, North Kerala, India: a cross sectional study - S. A., Thilak; A. K., Sarada; Neloopant, Sushrit A. (International Journal Of Community Medicine And Public Health, 2017)
Background: The proportion of elderly people aged 60 years and above is increasing in India alarmingly and they are at higher risk of developing neuropsychiatric problems if any associated comorbidities exist. The commonest neuropsychiatric problem is depression and if not diagnosed and treated early will lead to serious psychiatric illnesses, so this study was conducted to know the prevalence and factors associated with geriatric depression in rural Kannur. The aim was to determine the prevalence and the factors associated with depression among elderly in rural areas of Kannur, North Kerala, India. Methods: A cross sectional study was conducted at two Grama Panchayaths under the rural field practice area of Community Medicine department, Kannur Medical College, Kannur, Kerala, India. Convenient sampling method was used for the sampling. Data was collected using Geriatric Depression Scale (GDS) by visiting homes and rural health centre, descriptive statistics and associations were analysed. Results: Out of 250 elderly persons, 51.6% were males and 48.4% were females and prevalence of geriatric depression was 72.4%. The independent predictors of depression were elderly persons aged >70 years, financial dependency and with one or more comorbidities (p <0.05). Conclusions: The prevalence of geriatric depression is alarmingly high and the factors associated with geriatric depression were people aged >70 years, financial dependency and having one or more comorbidities. There is a need to strengthen the mental health programme in the primary health centres. Giving health education to family members to spend time with elderly, creating awareness about the availability of social security schemes, family support to the elderly may help in preventing depression.